Philology and Sacred: Church Slavonic Language in the Views of Mychailo Maksymovych - Yeremieiev, Pavlo (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Purpose. The article attempts to discover how and under the influence of what factors Mykhailo Maksymovych perceived and described the Church Slavonic language and how the scholar’s vision of this issue influenced other assessments and characteristics in his works. Methods. The study is based on the dichotomy of the sacred and the profane described in the phenomenology of religion. Based on published works by Mykhailo Maksymovych, his memoir, letters and unpublished notes, saved in the Institution of Manuscript of Vernadsky National Library of Ukraine (Kyiv), I attempt to find out whether the sacralisation of the Church Slavonic language took place in the mind of Mykhailo Maksymovych, and if so, how this sacralisation influenced his assessment of the place and role of this language in national life.Scientific novelty. The author reveals how Mykhailo Maksymovych’s religious views and worship experiences influenced his perception of the Church Slavonic language in his scientific works. The connection between Mykhailo Maksymovych's opinions on the Church Slavonic language and his assessments of the importance of other Slavic languages is revealed.Conclusions. Mykhailo Maksymovych sacralised the Church Slavonic language under the influence of his religious beliefs and prayer practices. This process resulted from rather archaic principles of thinking described in terms of the phenomenology of religion. Influenced by the sacralisation of the Church Slavonic language, Mychailo Maksymovych characterised its influence as positive without any philological arguments. Postulating the thesis about the particular impact of the Church Slavonic language on the formation of the Russian literary language, Mykhailo Maksymovych stressed its superiority to the other Slavic languages.